(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Sustainability in the fashion and textile industry is becoming a significant research focus due to global warming and climate change. However, more research is needed on consumers’ carbon emissions in the context of clothing consumers. This study focuses on consumers and develops a comprehensive accounting model of the carbon footprint of clothing consumption. A simulation experiment is conducted through surveys and empirical data to calculate the carbon emissions associated with consumers engaging in clothing purchase and clothing use. The sensitivity analysis examines the factors influencing carbon emissions at each stage. The finding reveals that in the overall carbon footprint of clothing consumers, clothing use has the highest impact than clothing purchase. The findings from this study offer valuable insights for consumers looking to reduce their carbon footprint during clothing purchase and use and also serve as a foundation for future research endeavours, which has great significance for the reduction of carbon emissions in society as a whole.